2020
DOI: 10.3390/ma13163607
|View full text |Cite
|
Sign up to set email alerts
|

Application of Elastic Waves and Neural Networks for the Prediction of Forces in Bolts of Flange Connections Subjected to Static Tension Tests

Abstract: There is a group of measurement techniques that can be used in the task of force identification in steel bolts. In this paper, the potential of elastic wave propagation signals was studied for possible application in force monitoring systems. A series of laboratory tests was carried out on flange connections subjected to static tensile tests. Each one contained six screws of the same diameter. Four bolts were equipped with washer load cells. Alternatively, selected bolts were equipped with piezoelectric transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the field of using sensors to determine the preload of the bolts, Nazarko et al [10,20] used piezoelectric transducers to develop a non-destructive testing method for determining the preload of the bolts. Herbst et al [21] innovatively designed a force-measuring bolt by integrating a force sensor directly into the bolt structure, allowing real-time monitoring of the bolt's stress state.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of using sensors to determine the preload of the bolts, Nazarko et al [10,20] used piezoelectric transducers to develop a non-destructive testing method for determining the preload of the bolts. Herbst et al [21] innovatively designed a force-measuring bolt by integrating a force sensor directly into the bolt structure, allowing real-time monitoring of the bolt's stress state.…”
Section: Introductionmentioning
confidence: 99%
“…Despite how interesting they are, they do not raise issues of sensor attachment influence on excited and registered signals. In the articles on the use of elastic waves [12,22], the authors take into account diverse sets of samples and the influence of sample characteristics on the wave parameters, but the issue of the influence of bonding on the excited wave is not discussed or considered. Potential discrepancies between the analyzed signals can be results from gluing the sensors, which was mentioned in [22], or the specimen surface roughness [7].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of experimental and numerical studies is reported in the papers in this Special Issue [1][2][3][4][5][6][7][8]. Nazarko and Ziemia ński [1] monitored the axial bolt forces by means of elastic wave propagation signals.…”
mentioning
confidence: 99%
“…A wide range of experimental and numerical studies is reported in the papers in this Special Issue [1][2][3][4][5][6][7][8]. Nazarko and Ziemia ński [1] monitored the axial bolt forces by means of elastic wave propagation signals. A series of laboratory tests were carried out on flange connections with six bolts, subjected to static tensile tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation